1996
DOI: 10.1136/gut.39.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrate concentration in infective gastroenteritis and inflammatory bowel disease.

Abstract: Background-In subjects on a low nitrate diet, plasma nitrate concentration and urinary nitrate excretion are thought to reflect endogenous nitric oxide (NO) production, and have been reported to increase during infective and inflammatory bowel disease. Aits-To compare the extent of NO production in patients with infective versus non-infective forms of bowel dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 17 publications
(3 reference statements)
3
31
2
Order By: Relevance
“…Studies in experimental animals also suggest a beneficial role of inducible NO synthase during Salmonella infection (25), and elevated production of NO has been detected in patients with bacterial gastroenteritis (29). The present observations indicate that synergistic antimicrobial activity can result from the combination of the phagocyte respiratory burst and NO synthase in vivo as well as in vitro.…”
Section: Discussionsupporting
confidence: 70%
“…Studies in experimental animals also suggest a beneficial role of inducible NO synthase during Salmonella infection (25), and elevated production of NO has been detected in patients with bacterial gastroenteritis (29). The present observations indicate that synergistic antimicrobial activity can result from the combination of the phagocyte respiratory burst and NO synthase in vivo as well as in vitro.…”
Section: Discussionsupporting
confidence: 70%
“…During this phase, NO provides microbicidal activity in concert with the relatively potent phagocyte respiratory burst. The role of NO in human host defense against Salmonella serovar Typhimurium is far less clear, but elevated production of NO has been detected in patients with bacterial gastroenteritis (10). Although most investigators have demonstrated NO production by human macrophages (43), the role of NO in the microbicidal activity of human macrophages remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Humans unquestionably produce dramatically elevated quantities of NO during infection and other inflammatory conditions (4,24). Nevertheless, in vitro treatment of human peripheral blood mononuclear cells with lipopolysaccharide and interferon-␥ fails to elicit NO production (15), even though these stimuli are highly effective in provoking murine macrophages to generate copious quantities of NO (19).…”
mentioning
confidence: 99%